Detection of Residual Levels and Associated Health Risk of Seven Pesticides in Fresh Eggplant and Tomato Samples from Narayanganj District, Bangladesh - Md. Nur Alam, Md. Nur Alam; Chowdhury, M. Alamgir Zaman; Hossain, M. Sabir; Rahman, Mohammad Mijanur; Rahman, M. Abdur; Siew, Hua Gan; Khalil, Md. Ibrahim (Hindawi Publishing Corporation, 2015)
Residual levels of seven frequently used pesticides were investigated in 140 samples of two common vegetables, eggplants and tomatoes, from agricultural fields in the Narayanganj district of Bangladesh.The analysis of pesticide residues was performed by high-performance liquid chromatography with photodiode array detection.Alarge percentage of the eggplants (50%) and tomatoes (60%) from the Narayanganj district were contaminated with pesticides, and all of the levels were above the maximum residual limit (MRL) proposed by the EC regulation. Diazinon was the most common (35%) pesticide detected in the vegetable samples at a concentration of 45–450 times higher than the MRL. The health risk index for diazinon was highest for both eggplant and tomato samples, which may be due to its physiochemical properties. Fenitrothion and linuron are the two second most common types of pesticides detected in the vegetable samples. Regular monitoring of the use of common pesticides on vegetables should be conducted.